Optimization of DIC-Tripolium Ecofriendly Extraction Process: Recovery of Hesperidin from Orange Byproducts, Antioxidant and α-Amylase Inhibition of Extracts - Mariem Ben Abdallah; Morad Chadni; Nouha M'hiri; Fanny Brunissen; Nesrine Rokbeni; Irina Ioannou; Karim Allaf; Colette Besombes; Nourhene Boudhrioua (MDPI AG, 2023)
This study aimed to investigate the effect of an innovative ecofriendly process-instant controlled pressure drop technology, also known as "détente instantanée contrôlée" or DIC-coupled with Tripolium extraction (DIC-Tripolium), on the hesperidin recovery, and antioxidant and antidiabetic activities of orange byproduct extracts. A DIC pretreatment was applied to partially dried orange byproducts (~16% wet basis). A central composite rotatable design (CCRD), composed of 13 experimental trials (four factorial points, four-star points, and five repetitions for the central point), was followed by a Tripolium process consisting of successive intermittent extraction periods using ethanol/water solvent at 20 ± 1 °C, 5 kPa for 5 min and m/v ratio = 5 g/50 mL. The DIC pretreatment, coupled with the Tripolium process, increased the extractability of hesperidin (from 1.55- to 4.67-fold compared to untreated DIC orange byproducts). The radical scavenging activities of the extracts were also enhanced or preserved in different DIC-Tripolium extracts. The α-Amylase inhibition percentage varied between 55.6 ± 0.02 and 88.30 ± 0.01% according to DIC-Tripolium conditions. The multi-criteria optimized condition of DIC-Tripolium extraction, allowing for the maximization of the hesperidin content, radical scavenging activities, iron chelating activity, and α-amylase inhibition of extracts, corresponds to a DIC saturated steam pressure of 599.4 kPa and a DIC pretreatment time of 38 s.